Relationship of Self Care With Blood Sugar Rate On Patients With Diabetes Mellitus At Herna Rsu Medan - Martaulina Sinaga (Institute of Computer Science (IOCS), 2021)
DM that does not get a good handler can cause an increased risk of acute and chronic complications. So self-care is needed to reduce the risk of complications. This study aims to determine the relationship between Self-Care and Blood Sugar Levels in Patients with Diabetes Mellitus at Herna Medan General Hospital in 2019. Method: Type of analytic observational study with a cross-sectional design. The population was sampled, namely all diabetes mellitus sufferers who came for treatment from September to October 2019 at Herna Medan General Hospital, totaling 60 respondents. The data analysis technique uses the chi square statistical test . Results: The majority of self-care performed by people with Diabetes Mellitus at Herna General Hospital had insufficient self-care as many as 38 respondents (66.3%). 35 respondents (58.3%) had abnormal blood sugar levels of Diabetes Mellitus sufferers at Herna General Hospital. there is a relationship between poor self-care and abnormal blood sugar levels with a value of p = 0,00. Conclusion: there is a relationship between self-care and blood sugar levels in people with diabetes mellitus at Herna General Hospital in Medan. It is recommended that Herna Medan General Hospital improve health promotion strategies on Diabetes Mellitus Self-Care through leaflets, posters so that cases of Diabetes Mellitus with complications can be reduced